Liquidity and Capital Adequacy Impact on Profitability in Indonesian Conventional Banks - Dede Puspa Pujia; Dadang Abdullah; Pipih Juslisha; Shopie Febrianti; Lisa Iskia; Sherina Septiana; Syifa Nur Febriandini (Universitas Muhammadiyah Tangerang, 2026)
Profitability remains a central indicator of banking performance, reflecting the ability of institutions to sustain growth and resilience in competitive markets. In the Indonesian context, conventional banks face increasing pressure to balance liquidity and capital adequacy in order to optimize returns while maintaining financial stability. This study aims to analyze the influence of liquidity, measured by Loan to Deposit Ratio (LDR), and capital adequacy, measured by Capital Adequacy Ratio (CAR), on profitability (ROA) among conventional banking sub-sector companies listed on the Indonesia Stock Exchange. Employing a quantitative approach, the research uses purposive sampling with secondary data and applies multiple linear regression analysis to examine 30 firm-year observations. The findings reveal that liquidity does not exert a significant effect on profitability, whereas capital adequacy demonstrates a positive and significant impact. Simultaneously, both variables contribute to explaining variations in profitability, underscoring the importance of capital strength in enhancing bank performance. The novelty of this study lies in its empirical evidence from Indonesian conventional banks, highlighting CAR as a critical determinant of profitability. The results provide practical insights for regulators and bank management in designing strategies that prioritize capital adequacy as a driver of sustainable profitability.